2015
DOI: 10.1177/1420326x15585327
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an air curtain system for local pit environmental control for relic preservation in archaeology museums

Abstract: Indoor environmental control has been proven to be a critical consideration for preserving in situ unearthed relics in archaeology museum. An air curtain system has been proposed to separate the local environment of funerary pit from its large-space exhibition hall. The isolation efficiency of the air curtain is formulated by using stream function method in this study. The geometrical dimensions and jet flow parameters were investigated in this study through the theoretical formula, to determine their effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…This has led to obtaining a correlation coefficient of 0.9886 ( Figure 12), which is quite close to the previous relation. These results are considered in Equation (22). It was observed that some variables were very close to the unit or to 0.5.…”
Section: Influence Of E +1 − Hjk L On the Average Speed At The Doomentioning
confidence: 99%
“…This has led to obtaining a correlation coefficient of 0.9886 ( Figure 12), which is quite close to the previous relation. These results are considered in Equation (22). It was observed that some variables were very close to the unit or to 0.5.…”
Section: Influence Of E +1 − Hjk L On the Average Speed At The Doomentioning
confidence: 99%
“…This study noticed about 15% savings in the electricity bill for the Amsterdam Museum. Luo et al [18][19][20][21] proposed a variety of environmental control systems for preservation of historical relic sites (e.g., air curtain system, local displacement ventilation system, capillary radiation system) in China. These systems can effectively support the local environmental control for the historical relic sites and substantially reduce the energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…22 Air curtains have also been used in practical applications such as air-conditioned rooms, food storage, refrigeration and aircraft and relic preservation. [23][24][25][26] Research on air curtains started in the 1960s, and mathematical models for heat transfer across air curtains were proposed. [27][28][29] Based on research for identifying an optimal jet momentum of an air curtain, [30][31][32] many studies consistently reported its applications, energy efficiency and numerical model development.…”
Section: Introductionmentioning
confidence: 99%